PRABOWO SUBIANTO DAN SOEKARNOISME - F.P. Amalo, Gentry (Interaksi: Jurnal Ilmu Komunikasi, 2015)
AbstractThe spectacle of 2014 Indonesian Presidential Election was not solely a collection of Prabowo’sself-image, but more likely of social relation which were mediated through Soekarno’s image. Socialrelation has shifted further into commodity relation, where the heroic, anti-capitalist Soekarno’sself-image; being used as political commodity for Prabowo’s interest in taking over all aspects ofSoekarno’s life.Prabowo has impressed his admirer to copy and reproduce his self image during the campaign.The image that Prabowo has tried to present, as to dressed up similarly to Soekarno, was just apolitical performance in a battle to win the presidential seat.